Increasing the yield of pure hydrogen generated in the chemical loop reforming of methanol by using the oxygen carrier catalyst bi- layer arrangement - Hossein Khani; Nahid Khandan; Mohammad Hasan Eikani; Ali Eliassi (شیمی کاربردی روز)
The production of pure H2 for polymer fuel cells was studied by the chemical loop reforming of methanol in the presence of 0.3CoFe2O4-0.4ZrO2 as an oxygen carrier in a micro-channel reactor. The results of this study showed that the production of pure H2 is possible only if the coke deposition is controlled. By optimizing the reduction time to 7 minutes, the coke deposition controlled and pure H2 flow was produced with an average yield of 2.6%, which was an interesting result and so far this degree of purity of H2 has not been reported by the chemical loop reforming of methanol. To increase the yield of pure H2 in this study, a two-layer catalyst concept is proposed in the form of an additional layer coating with high resistance to coke and suitable reactivity with methanol from NiO/MgAl2O4 to 10% on 0.3CoFe2O4-0.4ZrO2 layer. Optimization of various parameters using the concept of double-layer oxygen carrier showed that the use of 20% nickel concentration with a reduction time of 11 minutes increased the yield of H2 with 100% purity, which increased by 42% in the double-layer arrangement compared to the single-layer state, and it is a promising result for the concept of bi-layer oxygen carrier in this process.